Isolation and solubilization of proteins after TRIzol® extraction of RNA and DNA from patient material following prolonged storage - Amanda B. Hummon; Sharlene R. Lim; Michael J. Difilippantonio; Thomas Ried (BioTechniques)
A systems approach is being applied in many areas of the biological sciences, particularly in cancer research. The coordinated, simultaneous extraction of DNA, RNA, and proteins from a single sample is crucial for accurate correlations between genomic aberrations and their consequences on the transcriptome and proteome. We present an approach to extract and completely solubilize up to 98% of the total protein recovered from archived samples following TRIzol® isolation of RNA and DNA. We also demonstrate using polyacrylamide gel electrophoresis (PAGE) and Western blot analysis that the proteins, representing both a wide molecular weight range and some posttranslational modifications, such as protein phosphorylation, remain stable in phenol-ethanol for up to 3 years at −20°C.